2019
DOI: 10.1016/j.celrep.2019.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Sox2 and Klf4 as the Functional Core in Pluripotency Induction without Exogenous Oct4

Abstract: Highlights d Polycistronic Sox2 and Klf4 reprogrammed mouse somatic cells to iPSCs d Stoichiometry of Sox2 and Klf4 is essential for S 2A K 2A M reprogramming d 2 MEFs and NPCs adopted convergent trajectories in S 2A K 2A M reprogramming d Sox2 and Klf4 cooperatively bound to induce the pluripotency network

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 45 publications
1
36
0
2
Order By: Relevance
“…In line with the fact that refractoriness to chemotherapy is a hallmark associated with cancer stemness [41][42][43], we could further show that MCT1-driven lactate uptake favors stemness properties. Thus, under glucose restriction and exposure to lactate, PDAC cells are characterized by a greater capacity of colony formation that is seen after their re-exposure to normal glucose supply.…”
Section: Discussionsupporting
confidence: 81%
“…In line with the fact that refractoriness to chemotherapy is a hallmark associated with cancer stemness [41][42][43], we could further show that MCT1-driven lactate uptake favors stemness properties. Thus, under glucose restriction and exposure to lactate, PDAC cells are characterized by a greater capacity of colony formation that is seen after their re-exposure to normal glucose supply.…”
Section: Discussionsupporting
confidence: 81%
“…4 C,D). Sox2 is a key transcription factor in the maintenance and development of pluripotency 42 , 43 . Stage specific embryonic antigen 1 (SSEA1) is an early marker of the development of pluripotency during the development of induced pluripotent stem cells from mouse embryonic fibroblasts (MEFs) 44 .…”
Section: Resultsmentioning
confidence: 99%
“…In order to understand how USP9X may act upon target genes, we searched for transcription factor motifs enrichment using the oPOSSUM web-based platform. We revealed that genes deregulated in Usp9X KD cells were enriched in their promoter for DNA motifs of core pluripotency transcription factors, including KLF4, ZFP281 and MYC ( Supplementary Table 4G-H) [56][57][58]. This suggests that USP9X transcriptional targets are also regulated by pluripotency factors.…”
Section: Usp9x Regulates Pluripotency Transition and Its Depletion Comentioning
confidence: 87%